2015
DOI: 10.1111/bjh.13818
|View full text |Cite
|
Sign up to set email alerts
|

PhaseIItrial of R‐CHOPplus bortezomib induction therapy followed by bortezomib maintenance for newly diagnosed mantle cell lymphoma:SWOGS0601

Abstract: Summary Bortezomib is active in mantle cell lymphoma (MCL), with approval in upfront and relapsed settings. Given inevitable recurrence following induction chemoimmunotherapy, maintenance approaches are a rational strategy to improve clinical outcomes. We conducted a phase II study to evaluate the safety and efficacy of six cycles of R-CHOP plus bortezomib (1.3 mg/m2 days 1 and 4 of 21 day cycles) followed by bortezomib maintenance (1.3 mg/m2 days 1, 4, 8, and 11 every 3 months for 2 years). Sixty-five eligibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 47 publications
2
26
0
Order By: Relevance
“…Recent SWOG experience in this patient population in S0213 (Bernstein , et al 2013) and S0601 (Till , et al 2016) suggested a historical 2-year PFS of 68%. In order to proceed with development, the observed 2-year PFS on the corresponding arm must be at least 75%.…”
Section: Methodsmentioning
confidence: 92%
“…Recent SWOG experience in this patient population in S0213 (Bernstein , et al 2013) and S0601 (Till , et al 2016) suggested a historical 2-year PFS of 68%. In order to proceed with development, the observed 2-year PFS on the corresponding arm must be at least 75%.…”
Section: Methodsmentioning
confidence: 92%
“…Bortezomib might also benefit patients with MCL as a maintenance therapy, as suggested by the results of a phase II trial 68 , in which R-CHOP was administered as induction therapy, followed by bortezomib as maintenance therapy. This treatment was well tolerated, and the reported toxicities were mainly haematological and grade 3 or higher peripheral neuropathy (in 5% of patients) 69 . With this regimen, the 5-year overall survival and 2-year PFS were 66% and 62%, respectively, indicating a more favourable response than that observed in previous studies in patients with MCL treated only with R-CHOP 68,70 .…”
Section: Introductionmentioning
confidence: 96%
“…The use of bortezomib is not approved for this indication, but this agent is often used in clinical practice in the first-line and relapsed and/or refractory settings. Investigators conducting three phase II studies 69,71,72 testing rituximab and bortezomib combinations in patients with newly diagnosed Waldenström’s macroglobulinaemia reported response rates of 66–85%, with responses occurring in the first 2–3 months of treatment 7173 . A randomized phase III trial 74 evaluating the addition of bortezomib to a dexamethasone, rituximab and cyclophosphamide regimen is currently ongoing, and results from this study should be reported in the next few years, and will hopefully help to clarify the role of bortezomib in the first-line setting (Table 5).…”
Section: Introductionmentioning
confidence: 99%
“…A recent phase 2 study added bortezomib to standard R-CHOP therapy followed by 3 monthly maintenance blocks for 2 years. 31 The results appear superior to R-CHOP alone, but a recent randomized trial shows no benefit for the addition of bortezomib following autologous transplantation, 32 suggesting that it seems unlikely that there is any real benefit for the use of bortezomib in this setting. For the transplantineligible patients, bortezomib has been incorporated into the R-CHOP regimen by substituting it for vincristine (VR-CAP).…”
Section: Impact Of Novel Agentsmentioning
confidence: 99%